Evidence for a hardwater radiocarbon dating effect, Wonder Lake, Denali national park and preserve, Alaska, U.S.A. - Child, Jonathan; Werner, Al (Géographie physique et Quaternaire)

(untitled) (Les Presses de l'Université de Montréal, 1999)
Abstract Anderson et al. (1994) present a late Pleistocene/Holocene pollen record for lacustrine sediment cores retrieved from the north end of Wonder Lake, Denali National Park and Preserve, Alaska. Bulk radiocarbon age estimates obtained during their study suggest that either a Picea refugium persisted in the foothills of the north Alaska Range near Wonder Lake during the Late Wisconsinan, or that bulk radiocarbon age estimates are inaccurate. Subsequent cores recovered from Wonder Lake (and a near-by kettle pond) have been correlated to the Anderson et al. core and age dated using Atomic Mass Spectrometry (AMS) radiocarbon age estimates. AMS radiocarbon ages suggest that bulk radiocarbon ages from Anderson et al. (1994) are affected by hardwater conditions in Wonder Lake causing them to appear greater than 2000 14 C years too old. The corrected core chronology is consistent with documented regional vegetation changes during the glacial/interglacial transition and does not require a local Picea refugium in the Wonder Lake area during the Late Wisconsinan.